Visual and Verbal Processes in Right-Left Confusion: Psychometric and Experimental Approaches - Tagami, Ubuka; Imaizumi, Shu (Frontiers in Psychology, 2021)
Errors in discriminating right from left, termed right-left confusion, reflect a failure in translating visuospatial perceptions into verbal representation of right or left (i.e., visuo-verbal process). There may also be verbo-visual process, where verbal cues are translated into visual representations of space. To quantify these two processes underlying right-left confusion, Study 1 investigated the factor structure of the Right-Left Confusability Scale, which assesses daily experiences of right-left confusion. Exploratory factor analysis suggested that these two processes and another factor reflecting mental rotation underlie right-left confusion. Study 2 examined correlations between the (sub)scale scores and performance on orientation judgement tasks reflecting visuo-verbal and verbo-visual processes. Overall, self-reported measures were not associated with the behavioral performances presumably reflecting the two processes. These results suggest that the cognitive mechanisms underlying right-left confusion can be classified into visuo-verbal and verbo-visual processes and mental rotation, although their psychometric and behavioral indices might be distinct. Further studies may develop better assessments of right-left confusion reflecting these processes.